Brucellosis In trade cattle in Lagos State: an investigation of two abbatoirs. (2009)
brucellosis affects domestic and wild animals as well as humans (charters,1980). Humans are usually affected due to zoonotic transmission from animals (mostly ruminants). Bovine brucellosis is usually caused by brucella abortus, less frequently by B. melitensis and rarely by B. suis (FAO,2003). it is usually manifested by abortion, with excretion of the organisms in uterine discharges and in milk. diagnosis depends on the isolation of brucella sp. from aborted material, udder secretion or from tissues removed at post-mortem examination. on the other hand, brucella antigens can be demonstrated through specific cell mediated or serological reactions(FAO,2003) the disease is endemic in Nigeria's livestock (Adamu and Ajogi,1999; Ishola and Ogundipe,2001) and serological prevalence rates of between 0.20% and 79.70% have been reported in various parts of the country 9Ocholi et al.,1977; Falade 2002; Cadmus et al;2006), therefore pointing at its public health implications. Lagos state is the second most populous state in Nigeria (NPC,2006) and the economic nerve centre of the nation. beef constitutes a major source of protein for the people in the state and equally a ready source of transmission of zoonotic diseases. since the last documented report of bovine brucellosis in Lagos state was about three decades ago(Esuruoso and ayanwale,1980), we therefore sought to determine the current status of the diseases among trade cattle in the state.